Dickens's London : Perception, Subjectivity and Phenomenal Urban Multiplicity - Wolfreys, Julian, 1958- (Edinburgh critical studies in Victorian culture., 2019)
This exploration of the streets of Dickens's London opens up new perspectives on the city and the writer. Taking Walter Benjamin's Arcades Project as an inspiration, Dickens's London offers an exciting and original project that opens a dialogue between phenomenology, philosophy and the Dickensian representation of the city in all its forms. Julian Wolfreys suggests that in their representations of London - its streets, buildings, public institutions, domestic residences, rooms and phenomena that constitute such space - Dickens's novels and journalism can be seen as forerunners of urban and material phenomenology. While also addressing those aspects of the urban that are developed from Dickens's interpretations of other literary forms, styles and genres, Dickens's London presents in twenty-six episodes (from Banking and Breakfast via the Insolvent Court, Melancholy and Poverty, to Todgers and Time, Voice and Waking) a radical reorientation to London in the nineteenth century, the development of Dickens as a writer, and the ways in which readers today receive and perceive both.